The Effect of Jigsaw Technique of Cooperative Learning and Personality Differences on The Reading Competency of Grade-Nine Students Of SMP Santo Yoseph Denpasar In Academic Year 2015/2016. - ., MARIA YASINTA SITI; ., PROF. DR. I KETUT SEKEN, M.A.; ., DR. NI MADE RATMININGSIH, M.A. (Jurnal Pendidikan Bahasa Inggris Indonesia, 2016)
Maria Yasinta Siti (2016). The Effect of Jigsaw Technique of Cooperative Learning and Personality Differences on The Reading Competency of Grade-Nine Students Of SMP Santo Yoseph Denpasar In Academic Year 2015/2016. Tesis, Jurusan Pendidikan Bahasa Inggris, Program Pascasarjana, Universitas Pendidikan Ganesha Tesis ini telah diperiksa dan disetujui oleh Pembimbing I : Prof. Dr. I Ketut Seken , MA. dan Pembimbing II Dr. Ni Made Ratminingsih, MA Kata Kunci : jigsaw, kepribadian, kemampuan membaca Penelitian ini bertujuan untuk menguji apakah di antara siswa yang diajarkan dengan menggunakan teknik jigsaw dan teknik pembelajaran konvensional terdapat (a) perbedaan signifikan pada kompetensi membaca, (b) efek interaksi antara teknik jigsaw dan kepribadian pada kompetensi membaca siswa, (c) perbedaan signifikan pada kompetensi membaca siswa yang ekstrovert, (c) perbedaan signifikan pada kompetensi membaca siswa yang introvert. Penelitian ini dilakukan pada kelas IX SMP Santo Yoseph Denpasar. Penelitian ini menggunakan metode penelitian post-test only control group design. Populasi dari penelitian ini adalah 315 siswa kelas IX pada tahun akademik 2015/2016. Terdapat 4 kelas yang digunakan sebagai sampel. Setelah menyebarkan kuesioner kecemasan belajar, terdapat siswa yang dikelompokkan menjadi 2 grup, 56 siswa ekstrovert dan 56 siswa introvert. Pada masing-masing grup, 26 siswa diajarkan dengan menggunakan teknik jigsaw, sedangkan 26 siswa lainnya diajarkan dengan menggunakan teknik konvensional. Pada akhir pengajaran, tes kompetensi membaca diberikan pada siswa. Data kemudian dianalisa dengan menggunakan Two Way Anova dan Tukey Test. Hasil dari penelitian ini adalah untuk kelas VIII SMP Santo Yoseph Denpasar (a) terdapat perbedaan signifikan antara siswa yang diajarkan dengan menggunakan teknik jigsaw dan siswa yang diajarkan dengan teknik konvensional, (b) tidak ditemukan adanya efek interaksi antara teknik jigsaw dan kepribadian terhadap kemampuan membaca siswa, (c) pada siswa ekstrovert, terdapat perbedaan signifikan antara siswa yang diajarkan dengan menggunakan teknik jigsaw dan siswa yang diajarkan dengan teknik konvensional dan (d) Pada siswa introvert tidak terdapat perbedaan signifikan antara siswa yang diajarkan dengan menggunakan teknik jigsaw dan siswa yang diajarkan dengan teknik konvensional. Temuan ini diharapkan memberikan kontribusi pada kelas membaca Bahasa Inggris di Indonesia. Kata Kunci : : jigsaw, kepribadian, kemampuan membaca Maria Yasinta Siti (2016), The Effect of Jigsaw Technique of Cooperative Learning and Personality Differences on The Reading Competency of Grade-Nine Students Of SMP Santo Yoseph Denpasar In Academic Year 2015/2016. Thesis, English Education Department, Post Graduate Study Program, Ganesha University of Education This thesis has been supervised and approved by Supervisor I : Prof. Dr. I Ketut Seken, MA. and Supervisor II Dr.Ni Made Ratminingsih, MA. Key words : jigsaw. personality differences, reading competency This study aimed at examining whether or not between students who are taught by using Jigsaw technique and students who are taught by using conventional learning technique there is (a) a significant difference in students’ reading competency, (b) an interaction effect between jigsaw technique and students personality differences on students’ reading competency, (c)a significant difference in reading competency on extrovert students and (d) a significant difference in reading competency of introvert students. This study was conducted to the ninth grade students’ of SMP Santo Yoseph Denpasar. The study employed post-test only control group design. The population of the study was 315 ninth grade students in academic year 2015/2016. There were 4 classes were used as the samples. After conducting personality questionnaire, 104 students were used as samples which were categorized into 2 groups, 52 extrovert students and 52 introvert students. In each group, 26 students were treated by using Jigsaw Technique while the rest 26 students were treated by using conventional technique. At the end of treatments, reading competency tests were used to collect the intended data. The collected data were analyzed by using Two Way Anova and Tukey Test. The results indicated that for ninth grade students of SMP Santo Yoseph Denpasar (a) there is a significant difference in students’ reading competency between students who are taught by Jigsaw Technique and students who are taught by conventional learning technique, (b) there is no interaction effect between the teaching techniques and personality, (c) there is a significant difference of extrovert students’ reading competency between those who are treated by using Jigsaw technique and those who are treated by using conventional technique in favor of Jigsaw Technique and (d) There is no significant difference of introvert students’ reading competency between those who are treated by using Jigsaw technique and those who are treated by using conventional technique. keyword : Jigsaw, personality differences, reading competency